Elements of destination and their impacts on vacationers experience - Rashid, Basri (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2013)
It is common for tourists to evaluate their visit experience when they return from a destination. Tourist encounters with the different components at the destination will have some impacts on their knowledge and emotions which ultimately affect visit satisfaction.This article discusses the evaluation process of tourist visit experience by investigating their perceived performance of the destination facilities and the role of emotions on their visit satisfaction.This study collected data using survey method by disseminating questionnaires at two popular destinations in the North of Malaysia, namely Penang and Langkawi Island.Results of the analyses show that a number of destination elements influence tourist emotions 'which eventually effect their visit satisfaction'.This study would help many stakeholders especially the tourism and hospitality related businesses.Similarly, such findings will also benefit the society and local organizations as a strategy to enhance destination components performance and enrich tourist visit experience.